Rounding frequency and hospital length of stay for children with respiratory illnesses: A simulation study. Issue 12 (13th November 2013) - East, Joseph; Cator, Allison; Burns, Emily; Lynn O'Gara, Tara; Card, Jason; Cohn, Amy; Macy, Michelle
<x xml:space="preserve">Abstract</x> BACKGROUND Patient discharge from the hospital is linked to physician‐led rounds, whereas discharge from the emergency department (ED) is more fluid. The relationship between rounding and length of stay (LOS) has not been quantitatively described. OBJECTIVES To describe the arrival and discharge patterns in the ED and inpatient settings for children with respiratory illnesses and to explore how the timing and frequency of rounding could impact LOS. DESIGN/SETTING Retrospective administrative data analyses of visits for respiratory illnesses to a tertiary care pediatric ED from May 2007 to April 2010. METHODS ED visits for common respiratory conditions were selected based on International Classification of Diseases, 9th Revision, Clinical Modification codes, excluding complex comorbid conditions, severe illness, and intensive care unit admission. Discharge time was plotted against arrival time for the ED and inpatient unit. LOS was calculated. A Monte Carlo simulation model was developed to explore the influence of additional rounds on inpatient LOS. RESULTS Of the 5503 included visits, 1285 (23.4%) resulted in inpatient care. Discharges from the ED typically occurred 2 to 5 hours after arrival, whereas most inpatient discharges occurred between 11 am and 6 pm regardless of admission time. Simulating 1 additional rounding session decreased predicted inpatient LOS by approximately 5 hours. CONCLUSIONS In contrast to ED discharges that occurred around the clock, inpatient discharges for children with respiratory illnesses were concentrated during afternoon hours. Increasing rounding frequency may improve hospital efficiency but could result in unintended consequences such as fewer opportunities for patient education. Journal of Hospital Medicine 2013;8:678–683. © 2013 Society of Hospital Medicine